Effects of Emotional and Sensorimotor Knowledge in Semantic Processing of Concrete and Abstract Nouns - Newcombe, P. I.; Campbell, Cale; Siakaluk, Paul D.; Pexman, Penny M. (Frontiers in Human Neuroscience, 2012)
There is much empirical evidence that words’ relative imageability and body-object interaction (BOI) facilitate lexical processing for concrete nouns (e.g., Bennett, Burnett, Siakaluk, & Pexman, 2011). These findings are consistent with a grounded cognition framework (e.g., Barsalou, 2008), in which sensorimotor knowledge is integral to lexical processing. In the present study, we examined whether lexical processing is also sensitive to the dimension of emotional experience (i.e., the ease with which words evoke emotional experience), which is also derived from a grounded cognition framework. We examined the effects of emotional experience, imageability, and BOI in semantic categorization for concrete and abstract nouns. Our results indicate that for concrete nouns, emotional experience was associated with less accurate categorization, whereas imageability and BOI were associated with faster and more accurate categorization. For abstract nouns, emotional experience was associated with faster and more accurate categorization, whereas BOI was associated with slower and less accurate categorization. This pattern of results was observed even with many other lexical and semantic dimensions statistically controlled. These findings are consistent with Vigliocco, Meteyard, Andrews, and Kousta’s (2009) theory of semantic representation, which states that emotional knowledge underlies meanings for abstract concepts, whereas sensorimotor knowledge underlies meanings for concrete concepts.